The ages and rock mineral composition of the Pechenga eastern frame, the Kola Region - Nitkina, E. A.; Kaulina, T. V.; Kozlov, N. E. (2020)
The research and dating of rocks in the area of the Central Kola block (the Kola Peninsula) is due to the need to develop the Lyceum uranium ore area, the most promising for uranium mining in the Kola region, located in close proximity to the study area and composed of similar gneisses from the Kola series. Within the Central Kola block, Archean complexes are represented by granite-gneisses and migmatites with relicts of biotite-plagioclase, biotite-amphibole-plagioclase gneisses, amphibolites, garnet-biotite-plagioclase and aluminous gneisses containing interlayers of ferruginous quartzite (quartz metasomatites) of various capacities. The rocks are repeatedly metamorphosed in conditions from high-temperature steps of the amphibolite facies to the granulite facies. Geological and geochronological methods have established the sequence of geological processes manifested in the rocks of the Kola series of the northwest framing of the Pechenga structure. The results of U-Pb dating are determined by zircon grains of the following genesis: metamorphic – in gneiss; magmatic and metamorphic – in metagabbro; metamorphic and metasomatic – in quartz metasomatite. The data obtained have made it possible to establish the age sequence of geological processes: 2.8 Ga – the time of metamorphism of garnet-biotite gneisses; 2,722 ? 9 Ma – crystallization of granodiorites; 2,636 ± 41 Ma – the formation of aplitic granites; 2,620 ? 16 Ma – the emplacement of pegmatites; the age of aplitic granites and pegmatites marks the final stages of the Archean evolution of the region; 2,587 ± 5 Ma – the emplacement of gabbroids, 2,522–2,503 Ma – the period of the thermal process associated with the formation of quartz metasomatites during the metamorphism of gabbro and garnet-biotite gneisses; 2,507 ± 7 Ma – metamorphism, schist and budding of gabbroids. Изучение и датирование пород в районе Центрально-Кольского блока (Кольский полуостров) обусловлены необходимостью разработки Лицевского урановорудного района, наиболее перспективного в ...